Discovery of Early Cretaceous Sinuiju Biota in the Democratic People's Republic of Korea and comparison with Jehol Biota in China. (November 2022) - Won, Chol Guk; So, Kwang-Sik; Pak, Un Song; Ju, Il Yop; Ri, Chol Jun; Jon, Su Hyang; Ma, Jun
Abstract: In recent years, some important fossils of the Jehol Biota of Early Cretaceous age in north-eastern China have been recorded from the Lower Cretaceous Sinuiju Formation in the Sinuiju area (north-western part of the Democratic People's Republic of Korea. This discovery indicates that the biota from the Sinuiju Formation can be related to those from the Yixian Formation in western Liaoning Province, China. The palaeontological evidence in the Sinuiju Basin shows that the Jehol Biota is more widely distributed than previously thought and the fossils composing the Jehol Biota include a greater variety of animal and plant taxa than earlier known. In previous studies, the age of the Sinuiju Formation was considered to be Late Jurassic–earliest Cretaceous on the basis of limited fossil evidence. In contrast, it is now considered to be earliest Cretaceous based on the new fossil finds. During a recent field survey, abundant fossils were collected from the lacustrine deposits of this formation. The discovery of the Sinuiju Biota adds significant new data to the study of the geographical distribution and diversity of the Jehol Biota in north-eastern Asia.